2006
DOI: 10.1021/ic060903e
|View full text |Cite
|
Sign up to set email alerts
|

A Density Functional Theory Study of the Electronic Properties of Os(II) and Os(III) Complexes Immobilized on Au(111)

Abstract: We present a density functional theory (DFT) study of an osmium polypyridyl complex adsorbed on Au(111). The osmium polypyridyl complex [Os(bpy)2(P0P)Cl]n+ [bpy is 2,2'-bipyridine, P0P is 4,4'-bipyridine, n = 1 for osmium(II), and n = 2 for osmium(III)] is bound to the surface through the free nitrogen of the P0P ligand. The calculations illuminate electronic properties relevant to recent comprehensive characterization of this class of osmium complexes by electrochemistry and electrochemical scanning tunneling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…While detailed reasons are not fully understood at present, the different forces reflect higher bonding strengths for Os 3 þ than for Os 2 þ . Earlier DFT studies for a terpy analogue (2,2 0 -bipyridine) showed that structural changes caused by the central metal redox state switching are insignificant, when the complex is immobilized on Au(111) surfaces 42,43 . The Os-terpy s bonding might be stronger for Os 3 þ than for Os 2 þ but this would be counterbalanced in part by relatively poorer p-back donation in the oxidized state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While detailed reasons are not fully understood at present, the different forces reflect higher bonding strengths for Os 3 þ than for Os 2 þ . Earlier DFT studies for a terpy analogue (2,2 0 -bipyridine) showed that structural changes caused by the central metal redox state switching are insignificant, when the complex is immobilized on Au(111) surfaces 42,43 . The Os-terpy s bonding might be stronger for Os 3 þ than for Os 2 þ but this would be counterbalanced in part by relatively poorer p-back donation in the oxidized state.…”
Section: Resultsmentioning
confidence: 99%
“…The Os-terpy s bonding might be stronger for Os 3 þ than for Os 2 þ but this would be counterbalanced in part by relatively poorer p-back donation in the oxidized state. The electronic charge distribution over the complex is different in the two redox states, as charge is relocated from the periphery of the complex to the metal upon oxidation 42,43 . Besides, different ligand field stabilization energies (LFSEs) could be a factor.…”
Section: Resultsmentioning
confidence: 99%
“…In the electrochemical scanning tunneling spectroscopy configuration (i.e., STM tip not chemically attached to the molecule) there is now a collection of examples displaying a clear maximum in their tunneling current (I tunneling ) vs electrochemical potential relations. 13,15,[23][24][25][26][27]29,39 These have been well-modeled in terms of the KU relationship for two-step electron/hole transfer through the redox center in the STM−substrate gap. The situation is far from clear for measurements made in the in situ electrochemically gated BJ configuration (i.e., when the electrochemically active bridge molecule is chemically attached at one end to the STM tip and at the other end to the substrate).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Traditionally, various organic molecules functionalized with thiols have been investigated for this purpose. However, recently there has been some interest toward employing organometallic complexes containing Ru [21][22][23][24] and Os [21,[25][26][27][28][29][30][31][32][33] metal ions and ligands derivatized with thiols and amino groups for SAM formation. High stability coupled with very good photophysical and electrochemical behavior, as well as the possibility to have multielectron processes make them appealing candidates over conventional organic molecules.…”
Section: Introductionmentioning
confidence: 99%